Ответ:
-3;-2;1;2
Объяснение:
5. ![x^{2} +\sqrt{(x-2)^{2} } -4=0 x^{2} +\sqrt{(x-2)^{2} } -4=0](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2B%5Csqrt%7B%28x-2%29%5E%7B2%7D%20%7D%20-4%3D0)
При х<0</p>
![x^{2} +2-x -4=0 x^{2} +2-x -4=0](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2B2-x%20-4%3D0)
![x^{2} +x-2=0 x^{2} +x-2=0](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2Bx-2%3D0)
a=1 b=1 c=-2
D=1+4*2*1=1+8=9>0-2 корня
x1=-1-3/2=-4/2=-2
x2=-1+3/2=2/2=1
При а>0
![x^{2} +x-2 -4=0 x^{2} +x-2 -4=0](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2Bx-2%20-4%3D0)
a=1 b=1 c=-6
0-2" alt="x^{2} +x-6=0\\D=b^{2} -4ac=1+4*1*6=1+24=25>0-2" align="absmiddle" class="latex-formula"> корня
x1=-1-5/2=-6/2=-3
x2=-1+5/2=4/2=2
Ответ: -3;-2;1;2